Evaluation of the Implementation of an Inpatient Electronic Medical Record System Using the Delone and Mclean - Asih Kundari; Budi Aji; Dwi Sarwani Sri Rejeki (Indonesian Journal of Global Health Research, 2025)
Background: Sumber Waras Hospital is committed to enhancing the quality of healthcare services through the implementation of an Electronic Medical Record (EMR) system. EMR is an essential tool for managing patient health data to improve service efficiency and effectiveness. However, its implementation still encounters various challenges, such as limited user training, interoperability issues, and inconsistent data quality. Therefore, this study aims to evaluate the success of the inpatient EMR system implementation at Sumber Waras Hospital using the Delone and McLean model approach. Research Methods: This research applied a descriptive quantitative method with a cross-sectional design. The study population consisted of 344 healthcare personnel, with a total of 77 respondents selected using the Slovin formula at a 10% margin of error. Result: The evaluation showed that system quality was categorized as moderate with an average score of 2.86. Information quality was also in the moderate category with a score of 3.15, followed by service quality at 3.14. System use was categorized as moderate with a score of 3.47, user satisfaction was categorized as good with a score of 3.50, and net benefits were categorized as moderate with a score of 3.30. Conclusion: The implementation of the inpatient EMR system at Sumber Waras Hospital is generally running quite well, although improvements are still required, particularly in system quality, information quality, and service quality aspects. The evaluation results are expected to serve as a reference for system improvements and user training efforts to enhance the overall quality of healthcare services. Keywords: Electronic Medical Records, Information System Evaluation, Delone and Mclean Bibliography: 43 (2017-2024).